1980
DOI: 10.1139/m80-140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected antineoplastic agents on the morphology of Candida albicans 5865

Abstract: When examined in an amino acid supplemented inorganic salts – glucose medium, the morphological development of Candida albicans 5865 is inhibited or delayed by several drugs common to cancer chemotherapy protocols. Yeast phase growth is inhibited by actinomycin D (100 μg/mL), bleomycin (500 μg/mL), 5-fluorouracil (1000 μg/mL), and hydroxyurea (1000 μg/mL). Germ tube formation was also inhibited by actinomycin D (100 μg/mL), and vincristine (100 μg/mL), doxorubicin and bleomycin (each at 500 μg/mL), and 5-fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…These effects were potentiated when these drugs were combined with AMB; actinomycin D-AMB combinations resulted in 90% loss in cell viability. 23 In another study, at drug concentrations typically used during therapy, C. albicans isolates exposed to methotrexate but not cyclophosphamide, cytarabine or dacarbazine produced significantly higher amounts of catalase (a marker of oxitatative stress) than did unexposed isolates. 24 As catalase activity in Candida spp.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These effects were potentiated when these drugs were combined with AMB; actinomycin D-AMB combinations resulted in 90% loss in cell viability. 23 In another study, at drug concentrations typically used during therapy, C. albicans isolates exposed to methotrexate but not cyclophosphamide, cytarabine or dacarbazine produced significantly higher amounts of catalase (a marker of oxitatative stress) than did unexposed isolates. 24 As catalase activity in Candida spp.…”
Section: Introductionmentioning
confidence: 98%
“…22,23 For example, both yeast-phase growth of and germ-tube formation by C. albicans were inhibited by treatment with actinomycin D, bleomycin, 5-FU and hydroxyurea at varying concentrations (100-1,000 μg/ml). 23 These effects were enhanced when the drugs were combined with AMB; in particular, actinomycin similar to the peak plasma concentrations of these agents that result from typical dosing; also, treatment with doxorubicin, vincristine and vinblastine inhibited Candida filamentation. These effects were potentiated when these drugs were combined with AMB; actinomycin D-AMB combinations resulted in 90% loss in cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…An anaerobic RNR activity was not detectable [190]. Proliferation inhibition caused by hydroxyurea was observed in cultures of Wangiella dermatitidis [193], Candida albicans [194], Neurospora crassa [195,196] and Schizophyllum commune [197][198][199].…”
Section: Algae Plants Fungi and Animalsmentioning
confidence: 99%
“…The direct effect of antineoplastic agents on C. albicans and other yeast was investigated by a number of workers. Land et al studied the effect of several antineoplastic agents on the morphology of C. albicans (58). They observed that germ tube formation was inhibited and forced into stasis by a number of these agents.…”
Section: Effect On the Microorganismmentioning
confidence: 99%